اختبار العلاقة بين الادخار المحلي و التضخم في الجزائر (1994- 2016) (مجلة الواحات للبحوث والدراسات, 2020)
The aim of this study is to investigate the short and the long-run relationship between home savings and inflation in Algeria for the period 1994 to 2016, the approach of (VAR) was utilized for the analysis. Results showed no statistically significant relationship found between the inflation and home savings in the short-run. Moreover, Since the result shows negative relationship between inflation and home savings in the long run. Keywords- home savings؛ Inflation؛ economic relationship؛ Algerian economy